Resolva, os sistemas pelo método que achar mais conveniente.
A)3x + y = 2
x - 2y = -4
B)x + y = 2
2x - 5y = -3


Resposta :

Resposta:

A)3x + y = 2

x - 2y = -4

[tex]x = - 4 + 2y \\ \\ 3 \times ( - 4 + 2y) + y = 2 \\ - 12 + 6y + y = 2 \\ - 12 + 7y = 2 \\ - 12 + 7y - 2 = 0 \\ - 14 + 7y = 0 \\ 7y = 14 \div (7) \\ y = 2 \\ \\ x = - 4 + 2 \times 2 \\ x = - 4 + 4 \\ x = 0 \\ \\ (x.y) = (0.2)[/tex]

B)x + y = 2

2x - 5y = -3

[tex]x = 2 - y \\ \\ 2 \times (2 - y) - 5y = - 3 \\ 4 - 2y - 5y = - 3 \\ 4 - 7y = - 3 \\ 4 - 7y + 3 = 0 \\ 7 - 7y = 0 \\ - 7y = - 7 \times ( - 1) \\ 7y = 7 \div (7) \\ y = 1 \\ \\ x = 2 - 1 \\ x = 1 \\ \\ (x.y) = (1.1)[/tex]